RefSeq curation and annotation of antizyme and antizyme inhibitor genes in vertebrates - Rajput, Bhanu (Nucleic Acids Res, 2015)
Polyamines are ubiquitous cations that are involved in regulating fundamental cellular processes such as cell growth and proliferation; hence, their intracellular concentration is tightly regulated. Antizyme and antizyme inhibitor have a central role in maintaining cellular polyamine levels. Antizyme is unique in that it is expressed via a novel programmed ribosomal frameshifting mechanism. Conventional computational tools are unable to predict a programmed frameshift, resulting in misannotation of antizyme transcripts and proteins on transcript and genomic sequences. Correct annotation of a programmed frameshifting event requires manual evaluation. Our goal was to provide an accurately curated and annotated Reference Sequence (RefSeq) data set of antizyme transcript and protein records across a broad taxonomic scope that would serve as standards for accurate representation of these gene products. As antizyme and antizyme inhibitor proteins are functionally connected, we also curated antizyme inhibitor genes to more fully represent the elegant biology of polyamine regulation. Manual review of genes for three members of the antizyme family and two members of the antizyme inhibitor family in 91 vertebrate organisms resulted in a total of 461 curated RefSeq records.